Desenvolvimento de metodologia para a determinação de contaminantes inorgânicos em polímeros por LA-ICP-MS - Voss, Mônica (2016)
In the present work a new calibration strategy was evaluated for further determination of As, Ba, Cd, Cr, Pb, Sr and Zn in food packaging by laser ablation and inductively coupled plasma mass spectrometry (LA-ICP-MS). The main innovation in this work was the use of nylon disks for calibration, due to its similarities with polymer samples regarding to carbon concentration and distribution through both materials. These conditions allowed the use of 13C as reference element during the analysis by LA-ICP-MS. The main advantage of the proposed procedure is the possibility of using aqueous standard solutions to carry out the calibration, which were dispensed on the nylon disks and dried before ablation, avoiding the time-consuming procedures of standard preparation for LA-ICP-MS analysis. Parameters as analyte signal normalization with 13C, carrier gas flow, laser energy, spot size, scan speed, pulse frequency and different treatments of the samples were investigated. Accuracy of LA-ICP-MS determinations were evaluated by analysis of certified reference materials of polymer samples, besides comparison with results obtained by ICP-MS after microwave-induced combustion. In this work, limits of detection obtained by LA-ICP-MS were 1 to 2 orders of magnitude higher than those usually obtained by ICP-MS with pneumatic nebulization. However, the procedure enabled the direct multielement analysis in polymer samples.